Modified Fracture Mechanics Approach for Hydraulic Fracturing Stress Measurements - Guiyun Gao; Chenghu Wang; Hao Zhou; Pu Wang (Geofluids)
Hydraulic fracturing (HF) test has been widely used to determine in situ stress. The use of a conventional continuum method for this purpose has raised considerable controversies concerning field tests, particularly in the determination of the maximum horizontal principal stress under preexisting fractures. Fracture mechanics methods are very promising when considering preexisting cracks. However, most fracture mechanics methods do not include the effects of confinement on fracture parameters that depend on confining stress. In the present paper, we proposed a modified approach based on fracture mechanics for stress determination considering the relation between fracture toughness and confining stress based on the Rummel and Abou-Sayed methods. Then, we conducted true triaxial hydraulic fracturing tests under different stress ratios for granite and sandstone specimens to verify the proposed approach. The observed typical pressure-time curves indicate that in the conducted hydraulic fracturing tests, the steady fracture growth was attained. Moreover, we demonstrated that the stress ratios influence crack orientations. The horizontal maximum principal stresses determined using the modified Rummel method achieve the lowest relative error compared with other considered stress estimation approaches. This modified fracture mechanics method could be used as a potential alternative approach to obtain a considerably more precise estimation of the maximum horizontal stress in hydraulic fracturing stress determination.